A Sheila’s Chaotic Personality Viewed from a Psychosocial Development Perspective - Umi Sholihah; Sri Haryanti; Suhud Eko Yuwono; Kustinah Kustinah (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
Sheila is a major character in One Child novel written by Torey Hayden. This study attempts to analyze the novel based on its’ structural elements and to explore Sheila’s chaotic personality based on psychosocial developmental perspective proposed by Erik H Erikson. This research belongs to qualitative research which employs textual data. Textual data are taken from two sources; namely the novel itself as primary data source and the other materials which are related to the study as secondary data source. The technique of data collection is library research. The technique of data analyzing in this study is descriptive. The result of this study shows that the structural elements of the novel present a unity. It appears in the exposition, complication, climax, and resolution of the story. Furthermore, the psychosocial developmental analysis shows Sheila’s chaotic personality mostly caused by her past traumatic experience in her early life. Sheila had past traumatic and chaotic personality namely Mistrust (in stage infancy: birth – 1 year), Shame and Doubt (in stage early childhood: 2-3 years), 3) Guilt (in stage preschool age: 4-5 years), and 4) Inferiority (in stage school age: 6-12 years). The early life of Sheila was not told clearly, but Hayden just told the crucial event and condition of Sheila that made her become destructive, uncontrollable child, and has chaotic personality. Sheila tried to solve her crisis to develop her healthy ego development.